2010
DOI: 10.1186/1471-244x-10-74
|View full text |Cite
|
Sign up to set email alerts
|

Database analysis of children and adolescents with Bipolar Disorder consuming a micronutrient formula

Abstract: BackgroundEleven previous reports have shown potential benefit of a 36-ingredient micronutrient formula (known as EMPowerplus) for the treatment of psychiatric symptoms. The current study asked whether children (7-18 years) with pediatric bipolar disorder (PBD) benefited from this same micronutrient formula; the impact of Attention-Deficit/Hyperactivity Disorder (ADHD) on their response was also evaluated.MethodsData were available from an existing database for 120 children whose parents reported a diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Improvements in core ADHD symptoms were less consistent in children than in the adults, although self-reported ratings of inattention improved more across both age groups on micronutrients as compared with placebo. Further, these results were consistent with other micronutrient studies documenting improved emotional regulation and reduced aggression in children (Adams et al, 2011;Frazier, Fristad, & Arnold, 2012;Kaplan, Hilbert, & Tsatsko, 2015;Mehl-Madrona, Leung, Kennedy, Paul, & Kaplan, 2010;Rucklidge, Gately, & Kaplan, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Improvements in core ADHD symptoms were less consistent in children than in the adults, although self-reported ratings of inattention improved more across both age groups on micronutrients as compared with placebo. Further, these results were consistent with other micronutrient studies documenting improved emotional regulation and reduced aggression in children (Adams et al, 2011;Frazier, Fristad, & Arnold, 2012;Kaplan, Hilbert, & Tsatsko, 2015;Mehl-Madrona, Leung, Kennedy, Paul, & Kaplan, 2010;Rucklidge, Gately, & Kaplan, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Other nutrients such as flavonols (found in fruits; van Praag et al, 2007) and the omega-3 fatty acid docosahexaenoic acid (DHA; Adams, Lawson, Sanigorski, & Sinclair, 1996;Freeman et al, 2006;Hibbeln, 1998) have been found to improve cognitive function, which may improve mood. There is also evidence that micronutrient formulas may have therapeutic benefits for children with mood disorders such as paediatric bipolar disorder and attention-deficit/ hyperactivity disorder (Rucklidge, Gately, & Kaplan, 2010). Conversely, foods with high contents of trans or saturated fat have been shown to adversely affect cognition (Greenwood & Winocur, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…2010; Jacka et al . 2011), as do a growing number of treatment studies in which use of a broad spectrum of nutrients ameliorated mood symptoms (Gately & Kaplan 2009; Rucklidge et al . 2010).…”
Section: The Relevance Of Nutrition To Mental Health and Neurodevelopmentioning
confidence: 99%